Training and Mentoring for Students of the TPQ Al-Qur'an Education Park, Bulu Village, Batang Regency in the Haflah Akhirussanah Performance - Arditya Prayogi; Singgih Setiawan; Ahmad Tabi'in; Moh. Muslih (As-sunnah: Jurnal Pengabdian Masyarakat, 2024)
Currently, the existence of the Al-Qur'an Education Park is important, because apart from being a place for religious learning, it can also accommodate other activities, especially in this case Islamic art. One of the moments of an Islamic performance is usually shown in the haflah Akhirussanah activity. Thus, this service activity is carried out in the form of accompanying and training TPA students to encourage children/students to appear confident and motivate children to achieve better achievements. This service activity uses the service learning method by providing direct guidance to the objects of service (TPA students). From the results of the activities, we got an idea that the haflah Akhirussanah event went according to the activities that had been planned. The students looked enthusiastic and enthusiastic in participating in a series of activities starting from preparatory exercises to holding the event. The students seemed to show seriousness and activeness in preparing various activities to be presented on stage. It is hoped that in the future all parties can provide a platform for these students to show their activeness.